EFEKTIVITAS PENGGUNAAN FLASHCARDS DALAM MEMPERKAYA KOSAKATA BAHASA INGGRIS SISWA - Puteri Najma; Nur Aeni; Baso Jabu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to investigate the effectiveness of using flashcards in enriching students’ English vocabulary at MTs. Al-Hidayah Makassar. A quantitative approach was employed with a pre-experimental design, specifically the One-Group Pretest-Posttest Design. The sample consisted of 25 students from Class VII A and Class VII B, selected through cluster sampling technique. The instruments used were a Multiple Choice Question (MCQ) test consisting of 25 items and a Pronunciation Test consisting of 5 words, both scored on a scale of 0-100 and averaged into one final score. The data were analyzed using descriptive statistics and a Paired Sample T-Test through SPSS Version 26 for Windows. The findings showed a significant improvement in students’ English vocabulary mastery, with the mean score increasing from 54.56 in the pre-test to 78.56 in the post-test. These results confirm that the use of flashcards was effective in enriching students’ English vocabulary at MTs. Al-Hidayah Makassar, making it a practical and affordable learning media for schools with limited facilities.